Building Job Satisfaction: The Integration of Mental Workload, Quality of Work Life, and Happiness - Jadmiko, Purbo; Anggraeni, Ade Irma; Fatimah, Fatimah; Zakiy, Muhammad; Susanto, Is (Sharia Business Management UIN Raden Intan Lampung, 2024)
This quantitative study investigates the impact of mental workload, quality of work life, and happiness at work on job satisfaction among prison officers at Lembaga Pemasyarakatan Kelas IIB Pariaman (n=47). Data were collected through a survey using validated scales. Confirmatory Factor Analysis (CFA) and Cronbach's alpha were employed to ensure the validity and reliability of the instruments. Multiple regression analysis using STATA 12 revealed that both quality of work life and happiness at work have significant positive effects on job satisfaction, while mental workload does not significantly influence it. These findings align with previous studies highlighting the importance of employee well-being in enhancing job satisfaction. Practical implications suggest that organizations should focus on improving quality of work life and fostering happiness at work to boost employee satisfaction, which can subsequently enhance organizational performance. However, mental workload should be managed carefully, considering its potential indirect impact on satisfaction.